Socio-economic factors and smallholder cassava farmers' access to credit in south-western Nigeria - Awotide, B.A.; Abdoulaye, Tahirou; Alene, A.; Manyong, Victor M. (University of Liege, 2019)
Résumé Facteurs socio-économiques et accès au crédit des petits producteurs de manioc dans le sud-ouest du Nigeria